Programmable Aperture Photography: An investigation into applications and methods - Chiranjan, Ashill (Department of Electrical Engineering, 2019)
The fields of digital image processing (DIP) and computational photography are ever growing with new focuses on coded aperture imaging and its real-world applications. Research has shown that coded apertures are far superior to traditional circular apertures for various tasks. A variety of coded aperture patterns have been proposed and developed over the years for use in various applications such as defocus deblurring, depth estimation and light field acquisition. Traditional coded aperture masks are constructed from static materials such as cardboard and cannot be altered once their shapes have been defined. These masks are then physically inserted into the aperture plane of a camera-lens system which makes swapping between different patterned masks difficult. This is undesirable as optimal aperture patterns differ depending on application, scene content or imaging conditions and thus would need to be changed quickly and frequently. This dissertation proposes the design and development of a programmable aperture photography camera. The camera makes use of a liquid crystal display (LCD) as a programmable aperture. This allows one to change the aperture shape at a relatively high frame rate. All the benefits and drawbacks of the camera are evaluated. Firstly the task of performing deblurring and depth estimation is tested using existing and optimised aperture patterns on the LCD. A light field is then captured and used to synthesise virtual photographs and perform stereo vision. Thereafter, exposure correction is performed on a scene based on various degrees of illumination. The aperture pattern optimised online based on scene content outperformed generic coded apertures for defocus deblurring. The programmable aperture also performed well for depth estimation using an optimised pattern and existing coded apertures. Using the captured light field, refocused photographs were constructed and stereo vision performed to accurately calculate depth. Finally, the aperture could adjust to the different levels of illumination in the room to provide the correct exposure for image capture. Thus the camera provided all the advantages of traditional coded aperture imaging systems but without the disadvantage of having a static aperture in the aperture plane.